Unlocking Waste Heat Potential for District Heating Systems: An Hourly Mapping Methodology - Menapace, Andrea; Anania, Daniele; Dalle Nogare, Giovanni; Paradiso, Rosanna; Cozzini, Marco; Moreno, Diana; Nielsen, Steffen; Sorknæs, Peter; Ernst, Gebetsroither; Kozlowska, Anna (International Journal of Sustainable Energy Planning and Management, 2026)
The transition towards climate-neutral energy systems requires exploiting local renewable and residual energy sources to decarbonise the heating and cooling sector. District Heating and Cooling Networks (DHCNs) are key infrastructures for integrating Waste Heat (WH) into urban energy systems, but comprehensive spatial data on WH availability are often lacking and difficult to retrieve. This study develops a methodology for mapping WH potential from both industrial and tertiary sectors, providing critical information for the decarbonisation and expansion of existing DHCNs. The approach combines open geographic datasets, statistical information, and literature-based coefficients within a structured workflow to estimate potential annual WH availability at different temperature levels, along with its hourly profiles. The outcome is a detailed spatio-temporal characterisation of WH, presented in a geospatial package containing the georeferenced annual WH potential, coupled with a dataset of hourly profiles for each activity during a typical meteorological year. The methodology is applied to a case study in Milan with three main objectives: first, to test and validate the reliability proposed approach; second, to discuss the implications of WH integration in the development of a DHCN modernisation scenario; and third, to assess the uncertainty of waste heat potential estimation through comparison with Danish and Austrian reference databases. Thus, this study offers a replicable framework for WH potential mapping, supporting decision-making and planning for sustainable DHCNs and urban energy transition strategies.